″Features of teaching the discipline ―Conflictology‖ to future Managers of Education″ - Perminova, A. (Problems of Engineer-Pedagogical Education, 2018)
The article deals with the issue of teaching the discipline ―Conflictology‖ to future managers of education. Peculiarities of teaching the discipline are characterized, namely the need for the acquaintance of future managers of education with the evolution of scientific views on conflictology and periods of its development (ancient times, the Middle Ages, the Renaissance, the New Times and the Epoch of Enlightenment, the first half of the XIX century, the second half of the XIX – early XX century; modern development of conflictology); assimilation of special scientific terminology in conflictology and awareness of the essence of its object and subject; determination of purpose, tasks, structure and content of the discipline ―Conflictology‖; familiarization with the methodology of teaching the discipline which should correspond to the following system: methodological principles; general scientific approaches; specific and general methods. Taking into account all the peculiarities of teaching the discipline will help future managers of education effectively absorb knowledge and skills and will positively influence the implementation of the relevant knowledge in their future professional life, while managing an education institution, its structural unit or staff in particular, or when conflict situations emerge, develop or are being resolved.